Peran Pasar dan Pemasaran Syariah dalam Mendorong Pertumbuhan Ekonomi Nasional - Rizka Amelia (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2026)
National economic growth is not solely determined by conventional industrial and financial sectors, but also by the strengthening of markets and marketing strategies grounded in ethical and justice-based values. In the Indonesian context, as the country with the largest Muslim population in the world, Islamic markets and Islamic marketing possess significant strategic potential to support inclusive and sustainable national economic growth. However, the utilization of this potential has not yet been optimal due to limited Islamic economic literacy, marketing innovation, and policy integration. This study aims to analyze the role of Islamic markets and Islamic marketing in promoting national economic growth. The research employs a library research method with a qualitative-descriptive approach through the analysis and synthesis of scientific literature, institutional reports, and relevant Islamic economic policies. The results indicate that Islamic markets play an important role in strengthening the real sector, increasing asset-based investment, and fostering the development of the national halal industry. Meanwhile, Islamic marketing contributes to building consumer trust, expanding market access, enhancing economic inclusion, and improving the competitiveness of halal products, particularly through the utilization of digital technology. The integration of Islamic markets and Islamic marketing is proven to form a just and sustainable Islamic economic ecosystem. This study concludes that Islamic markets and Islamic marketing are strategic instruments in promoting national economic growth based on Islamic values. The implications of this research emphasize the importance of policy synergy, institutional strengthening, and the enhancement of literacy and innovation in Islamic marketing to optimize their contribution to national economic development.